2019
DOI: 10.1136/bmjopen-2019-031054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a comprehensive prevention programme aimed at reducing incivility and verbal violence against healthcare workers in a French ophthalmic emergency department: an interrupted time-series study

Abstract: Objective and settingPrimary prevention, comprising patient-oriented and environmental interventions, is considered to be one of the best ways to reduce violence in the emergency department (ED). We assessed the impact of a comprehensive prevention programme aimed at preventing incivility and verbal violence against healthcare professionals working in the ophthalmology ED (OED) of a university hospital.InterventionThe programme was designed to address long waiting times and lack of information. It combined a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 48 publications
(57 reference statements)
0
28
0
Order By: Relevance
“…Of note Bayram et al 39 observed that ED doctors responses seemed to indicate that the type of hospital was influential in ED violence with it being more common in public, rather than private, hospitals. ED over crowdedness 27,29,31,40 and waiting times 27,29,30,41,42 emerged as key contributory factors to ED violence. Indeed Efrat-Treister et al 40 found that crowdedness was associated with a greater number of violent attacks.…”
Section: Environmental Contributory Factors To Violencementioning
confidence: 99%
See 1 more Smart Citation
“…Of note Bayram et al 39 observed that ED doctors responses seemed to indicate that the type of hospital was influential in ED violence with it being more common in public, rather than private, hospitals. ED over crowdedness 27,29,31,40 and waiting times 27,29,30,41,42 emerged as key contributory factors to ED violence. Indeed Efrat-Treister et al 40 found that crowdedness was associated with a greater number of violent attacks.…”
Section: Environmental Contributory Factors To Violencementioning
confidence: 99%
“…One such study observed a reduction in ED violence was with the use of a specifically designed ED intervention programme. 42 This was designed to address long waiting times and provide more transparent and visible information to patients and attendees. It combined a computerized triage algorithm linked to a waiting room patient call system, signage to assist patients to navigate in the ED, educational messages broadcast in the waiting room.…”
Section: Management and Control Of Violencementioning
confidence: 99%
“…29 30 A previous multicomponent programme conducted in an emergency unit has shown the potential interest of a mediator in response to situations of violence. 31 Before setting up a mediation intervention, it is necessary to study the experiences about violence among the professionals who will be in contact with the mediators. Knowing these experiences makes it possible to adapt the mediation interventions to the difficulties and strategies already implemented by the professionals.…”
Section: Open Accessmentioning
confidence: 99%
“…16 Another study evaluated an electronic program addressing an algorithm of the waiting time of patients at a university hospital and noted a decrease in the incidence rate of violence among the health team. 17 Systematic reviews 18 19 have also sought to answer the question of the effectiveness of interventions carried out to prevent violence against health workers; however, authors 18 19 have found low to moderate evidence regarding prevention programs carried out in emergency departments. One study 18 evaluated the evidence according to the classification proposed by Oxford, 20 and another study 19 evaluated the evidence but did not present the tools used for the measurement.…”
Section: Open Accessmentioning
confidence: 99%
“… 16 Another study evaluated an electronic program addressing an algorithm of the waiting time of patients at a university hospital and noted a decrease in the incidence rate of violence among the health team. 17 …”
Section: Introductionmentioning
confidence: 99%